Pariwisata Indonesia dalam Menghadapi Peluang di Era Globalisasi (Studi Kasus: Desa Wisata Krebet Kecamatan Pajangan Kabupaten Bantul Provinsi DIY) - , DESY NUR AINI FAJRI, Drs. Usmar Salam, MIS ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research try to explain the actors who have roles in developing Tourism Village in global networking and the reasons why Krebet Tourism Village is more sustainable than other Tourism Village like Bobung and also how its mapping and synergy. The purpose of this research is to know who the actors involved in Krebet and why it is more sustainable in utilizing globalizationâs opportunity. Globalization has two sides that are challenges and opportunities. In this case, the important thing is that how a Tourism Village could be able to utilize the globalizationâs opportunity so a Tourism Village can increase its added value. Economic creative concept could be implemented in Krebet development so its product may compete in global market. Therefore, it needs the balancing between demand and supply because to fulfill the international market (tourism demand) is quite needed good packages in tourism supply. It needs the actors involvement in building global networking that are the government, privateâs roles and society. James Elliot (2002:3) in Tourism Politics and Public Sector Management gives the description of actorâs role in tourism policy. It concludes that the actorâs synergy is quite needed in Tourism Village development. The Local Government needs the other actors that are Tourism Association, Local Organization, Non Governmental Organization, Banking and Universityâs roles. In global area, there is United Nations World Tourism Organization (UNWTO) as International Organization that regulates service industry and eliminates the barriers for tourism development. Besides, there are a good synergy in the tourism organization of Krebet, networking and also Krebet Tourism Package. Those of all could develop added value of local products in the global market.